2023
DOI: 10.3389/fnut.2023.1104926
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the influence of withering degree on the dynamic changes in non-volatile metabolites and sensory quality of Longjing green tea by non-targeted metabolomics

Abstract: Withering is an important processing stage in green tea, which contributes to the tea flavor quality. The aim of this work was to comprehensively investigate the changes of chemical features and flavor attributes in Longjing green teas produced with five different withering degrees (moisture content of 75.05, 72.53, 70.07, 68.00, and 64.78%, w.b.). Combined with human sensory evaluation, electronic tongue and chromatic differences analysis, an assessment of the relationship between the withering degree and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(76 reference statements)
2
5
0
Order By: Relevance
“…Theaflavins were believed to play an important role in the astringency of tea infusion, which was confirmed by our study with the highest correlation coefficient (correlation coefficient > 0.83). From our results, we found that theaflavins contributed synergistically to the strong, bitter, and astringent taste in BT infusion, in line with previous research ( Shan et al, 2023 ). The presence of thearubigins also significantly contributed to the astringency of BT infusion ( Francis et al, 2008 , Liang et al, 2019 ), corroborating the findings of our study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Theaflavins were believed to play an important role in the astringency of tea infusion, which was confirmed by our study with the highest correlation coefficient (correlation coefficient > 0.83). From our results, we found that theaflavins contributed synergistically to the strong, bitter, and astringent taste in BT infusion, in line with previous research ( Shan et al, 2023 ). The presence of thearubigins also significantly contributed to the astringency of BT infusion ( Francis et al, 2008 , Liang et al, 2019 ), corroborating the findings of our study.…”
Section: Resultssupporting
confidence: 92%
“…In this study, theaflavins exhibited a significant correlation (P < 0.01) with color (yellow-green, yellow, orange and red). It is worth noting that the highest correlation coefficient was observed with the color yellow (465nm) ( Table 2 ), which aligns with previous studies ( Cui et al, 2022 , Shan et al, 2023 ). Additionally, the study showed ( Wang, Hua, Jiang, Wang & Yuan, 2020 ) that theaflavin, theaflavin 3,3′-digallate and theaflavin-3gallate were essential for color difference in black tea infusion, which was consistent with the results of this study.…”
Section: Resultssupporting
confidence: 91%
“…The representative different key compounds of phenolic acids, flavonols, and flavone/flavonol glycosides are exhibited in the metabolic pathway ( Figure 4 ). Quinic acid and p -coumaric acid have been reported to be mainly responsible for the bitterness and astringency taste in tea liquid [ 32 ]. Theogallin, as a derivative of quinic acid, can enhance the umami taste in tea infusions [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the non-targeted metabolomics analysis of secondary metabolites was conducted on WT and mutants ΔCcDFR and ΔCcOMT9 using liquid chromatography-mass spectrometry (LC–MS) technology (Bioincloud, Shenzhen), and the specific analytical method was done according to the methodology described by Shan et al (2023) .…”
Section: Methodsmentioning
confidence: 99%